Recall and Retention of Vocabulary Depth of Young Learners via PWIM - Lee, Bee Choo; Pandian, Ambigapathy; Rethinasamy, Soubakeavathi (UPM Press, 2020)
This quasi-experimental study explored the impact pictures had on the vocabulary depth knowledge of 7-year-olds in rural Malaysia. The Picture Word Inductive Model (PWIM) is designed to elicit words from students’ existing listening and speaking vocabularies while capitalising on a learner’s ability to think inductively. Modified and adopting a single-factor one-cycle design with PWIM as the independent variable, the intervention employed a pretest-posttest-delayed posttest control-group design. The subjects were comprised of 2 intact classes (n = 60), 1 class formed the Experimental group (n = 30) and another formed the Control group (n =30). The primary testing instrument, Read’s Word Associates Test (WAT), was specifically adapted to measure subjects’ vocabulary depth knowledge for recall and retention. Analysed results revealed superior recall and retention by the Experimental group, denoting the effectiveness of PWIM in enhancing vocabulary depth knowledge recall and retention among Malaysian young learners. Moreover, given vocabulary depth’s claim as the stronger predictor of language proficiency, the functionalities of such data in providing insights on effective measures to boost English language development, particularly among young learners, cannot be disputed. Keywords: PWIM, recall and retention, vocabulary depth, young learners.